IgA Nephropathy with Dominant IgA2 Deposition Accompanied by Mantle Cell Lymphoma - Kakeshita, Kota (Intern Med, 2020)
Malignant lymphoma is rarely complicated by secondary IgA nephropathy. We encountered a 74-year-old man with rapidly progressive glomerulonephritis due to IgA nephropathy with predominant deposition of IgA2, instead of IgA1, in the glomerulus that was eventually diagnosed as secondary IgA nephropathy due to mantle cell lymphoma. Renal impairment was improved by chemotherapy for the mantle cell lymphoma. IgA came from the colonic mucosa that was stimulated by the infiltrated lymphoma cells, instead of the tumor itself. We should consider mantle cell lymphoma as a cause of secondary IgA nephropathy, although its prevalence may not be very high.